The impact of socio-political developments on the Christians in the Middle East - Ahmad Fauzi Abdul Hamid (Proceedings of AICS - Social Sciences, 2013)
The subject of Christianity and Christians in the Middle East would seem to many be as oxymoronic as the topic of ‘Islam in the West’. While interest in Western-based Islam as faith-cum-political ideology and in Muslims as a distinctive polity has accelerated in line with global geo-political developments, relative ignorance regarding Christianity and Christians in the Middle East has been the norm rather than the exception. This paper is a modest attempt to redress the lack of attention hitherto given to Middle Eastern Christians as a multi-disciplinary research area.Keywords: Middle East, Christianity, Arab Christian, Eastern Christian, Muslim-Christian relations